2001
DOI: 10.1086/319214
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Gloves in the Prevention of Hand Carriage of Vancomycin-Resistant Enterococcus Species by Health Care Workers after Patient Care

Abstract: Gloving reduces acquisition of vancomycin-resistant Enterococcus species (VRE) on the hands, and it should be considered for routine inpatient care, even for contact with the intact skin of patients who may be colonized with VRE. However, gloving does not completely prevent contamination of the hands, and hand washing is necessary after glove removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(120 citation statements)
references
References 12 publications
2
110
0
6
Order By: Relevance
“…6,149150,206 g. After removing gloves. 147 " 149 h. After contact with blood or bodily fluids. 213,214 i.…”
Section: S E C T I O N 4 : R E C O M M E N D E D H a N D H Y G I E N mentioning
confidence: 99%
“…6,149150,206 g. After removing gloves. 147 " 149 h. After contact with blood or bodily fluids. 213,214 i.…”
Section: S E C T I O N 4 : R E C O M M E N D E D H a N D H Y G I E N mentioning
confidence: 99%
“…78,79,94,[132][133][134][135][136][137][138][139][140][141][142] For example, in studies conducted before glove use was common among HCWs, Ayliffe and colleagues 137 found that 15% of nurses working in an isolation unit carried a median of 1x 10 4 CFU of S. aureus on their hands; 29% of nurses working in a general hospital had S. aureus on their hands (median count, 3.8 x 10 3 CFU), while 78% of those working in a hospital for dermatology patients had the organism on their hands (median count, 14.3 x 10 6 CFU). The same survey revealed that 17-30% of nurses carried Gram-negative bacilli on their hands (median counts ranged from 3.4 x 10 3 CFU to 38 x 10 3 CFU).…”
Section: Organism Transfer To Health-care Workers' Handsmentioning
confidence: 99%
“…[922][923][924][925] Although recent studies suggest that improvements have been made in the quality of gloves, 919 the laboratory and clinical studies cited above provide strong evidence that hands should still be decontaminated or washed after glove removal. 73,123,139,204,520,914 …”
mentioning
confidence: 99%
“…Tangential support to this argument can be gleaned from the literature [11,29,34,43,70,75,84,87,89,92,100,104,125]. The hands of physicians are a known link in the transmission of nosocomial pathogens [70].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%
“…In the absence of gloves, there is a considerable increase in bacterial contamination of healthcare workers' hands after patient contact [75,87,100]. Numerous studies have investigated the rates of hand contamination after patient care, and hand contamination may occur even if gloves are worn [11,29,34,43,75,84,87,92,101,125].…”
Section: Avoiding Dressing Changesmentioning
confidence: 99%